FORMULASI KRIM ANTIJERAWAT EKSTRAK ETANOL BAWANG DAYAK (Eleutherina palmifolia (L.) Merr) - Husnani Husnani; Fitri Sri Rizki (Universitas Wahid Hasyim Semarang, 2019)
ABSTRACTDayak onion contains alkaloid compounds, flavonoids, saponins, tannins, glycosides, and triterpenoids which have anti-acne effects. This study aims to make cream formulas from Dayak onion ethanol extract and evaluate the physical quality characteristics of cream. The cream formulation from dayak onion extract was made with extract concentration of 100 mg/ml with stearic acid and triethanolamine as emulgator. Stearic acid and triethanolamine concentrations used were FI (6%: 2%), FII (12%: 3%), FIII ( 18%: 3%). The creams were evaluated for its physical quality characteristics, namely organoleptic, homogeneity, pH, dispersion, cream type and viscosity. From the evaluation of physical quality characteristics, it can be concluded that Formula III is the best formula that meets good cream quality requirements. The Dayak onion ethanol extract cream is an O/W type cream resulting in semi-solid, brown, organoleptic and dayak onion odor. In the homogeneity test there is no clumping on the cream preparation so that the preparation is homogeneous. The pH value is 6, so the cream is safe for the face. The spreadability of FIII is 7.52 cm, meets the requirements. The viscosity of F III is 32000 cPs, meets the requirements of a good cream preparation viscosity.Keywords: Formulation, Cream, Dayak Onion Extract (Eleutherine palmifolia (L.) Merr).